2018
DOI: 10.1186/s40795-018-0235-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green leafy vegetables powder on anaemia and vitamin-A status of Ghanaian school children

Abstract: Background: Nutritional anaemia and vitamin-A deficiency are public health issues confronting Ghanaian children. Their adverse effects are likely pronounced during the dry season when green leafy vegetables, rich-sources of iron and provitamin-A are scarce. This study assessed the effect of dried green leafy vegetables on anaemia and vitamin-A status of Ghanaian school children. Method: This was 3 months pretest, posttest nutrition intervention study. Children 4-9 years were randomized to receive or not receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
2
19
1
Order By: Relevance
“…20 Consumption of leafy green vegetables increases hemoglobin concentration, and has the potential to minimize the risk of anemia. 21 The correspondence between these findings could be due to poor dietary diversity across Ethiopia, which results in a dietary shortage of micronutrients, or due to the widespread inability to grow, source or afford green vegetables. In contrast, a study from the West Arsi Zone, Oromia Region, Ethiopia reported that the intake of green vegetables had no association with anemia.…”
Section: Discussionmentioning
confidence: 99%
“…20 Consumption of leafy green vegetables increases hemoglobin concentration, and has the potential to minimize the risk of anemia. 21 The correspondence between these findings could be due to poor dietary diversity across Ethiopia, which results in a dietary shortage of micronutrients, or due to the widespread inability to grow, source or afford green vegetables. In contrast, a study from the West Arsi Zone, Oromia Region, Ethiopia reported that the intake of green vegetables had no association with anemia.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size of 340 was estimated to identify anemic children, assuming a 33% mild and moderate anemia prevalence in South Ethiopia, precision of 0.5, and 95% confidence intervals. The sample size of the trial was calculated considering a mean difference of 0.7 in hemoglobin level [10], 1 standard deviation, power of 90%, alpha level of 0.05 with two sided test and an attrition rate of 12%. The total sample size of the trial was 100, with 50 children in each arm.…”
Section: Sample Sizementioning
confidence: 99%
“…The levels of Hb found in baseline were normal for men and women [38], however, this study showed that by incorporating a supplement with quelites into the diet, this nutritional biomarker can increase to 1.65 g/dL, concentrations that were higher compared to other studies. According to Egbi et al [39] in a supplementation study with children ages 6-9 years, it was found that the consumption of green leafy vegetables, among them, plants of the genera Amaranthus spp., increases Hb concentrations in supplemented children (12.1 g/dL) compared to the control group (11.3 g/dL) at the end of the study, minimizing the prevalence of anemia (supplemented: 33.3%; control: 57.5%) in participants treated with the powder preparation. On the other hand, Monroy-Torres et al [28] show that after supplementation in adolescents ages 12-15 years using a trademark based on grape, broccoli, and cranberry, Hb values increased 1 g/dL.…”
Section: Hb Concentrationmentioning
confidence: 99%
“…According to Egbi et al [39], micronutrients such as Zn, Fe, and β-carotene from wild plant sources (green leafy vegetable powder), lead to an improvement in nutritional status, increasing Hb values and decreasing the proportions of anemia. Concentrations of this indicator are attributable to the quality of the diet, mainly the less varied diets with low consumption of fruits and vegetables, and mostly made up of cereals and legumes, have high concentrations of anti-nutrients such as tannins and phytates, known as inhibitors of the absorption and bioavailability of iron and zinc [39]. Another factor involved is inflammation processes, which affects red blood cells and retinol serum levels [39].…”
Section: Hb Concentrationmentioning
confidence: 99%
See 1 more Smart Citation